Hot corrosion performance of bare and pulsed current welded Fe-based A-286 alloy in chlorine and sulphur environment. (April 2022) - Muthu, S M; Dinek, R; Mohan, P; Jithesh, K; Arivarasu, M
This present research work focuses on the hot corrosion performance of the base metal, weldment, and weld metal of A-286 alloy in sodium sulphate (Na2 SO4 )–5% sodium chloride (NaCl)–7.5% sodium metavanadate (NaVO3 ) (3SM) atmosphere at 700 °C. A pulsed current gas tungsten arc welding process is employed to make a similar joining of A-286 alloy using the filler material ERNiCrMo-3. The corrosion kinetics of the specimens has been determined using the thermo-gravimetric technique. The phase compositions of the reaction products are studied by X-ray diffraction, and the surface morphology of the scales is explored by scanning electron microscope analysis. The corroded samples are subjected to a cross-sectional study to ensure the corrosion attack and scales thickness using a SEM with elemental mapping technique. The result indicates that weldment showed better corrosion resistance than bare metal. A thick oxide scale could be found in the bare metal specimen than the weld metal. In the case of base metal, the formation of non-adherent and porous iron (III) oxide (Fe2 O3 ) leads to rapid corrosion. The weight gain of weldment is about 1.96 and 1.13 times less than bare alloy and weld metal.